Analisis Higiene Sanitasi Penjamah Makanan dan E.Coli Air Minum di Kantin Universitas Islam Sumatera Utara: Sanitary Hygiene Analysis of Food Handlers and E.Coli Drinking Water in The Canteen of The Islamic University of North Sumatra - Muhammad Rezebri (Media Publikasi Cendekia Indonesia, 2023)
Drinking water is one of the important sources for the human body's needs to support activities. The purpose of this study was to determine the sanitary hygiene of food, the personal hygiene of handlers, and the content of E.Coli in drinking water in the canteen of Islamic university xxx north Sumatra. This study used descriptive survey research. The location of this study is a canteen at the Islamic university xxx, north Sumatra. The sample in this study was ten canteens and 300 students, where 30 students were interviewed in each canteen. The data analysis of this study is a descriptive univariate analysis and E.Coli laboratory test. The result of this study was that two canteens did not meet the sanitary requirements of equipment, ten did not meet the sanitary requirements of ready-made food, and four did not meet the sanitary requirements of housing. Of the ten food handlers, 10 in the ten canteens do not meet the personal hygiene requirements of food handlers. The results of the E.Coli test found that the drinking water in 10 canteens contained E.Coli with the lowest level of 4 CFU / 100ml and a maximum of 28 CFU / 100ml, which did not meet the drinking water quality requirements. Students' perceptions regarding food sanitation and handlers have been good, with an average score of 260.6%. It is expected that the government conduct inspections of canteens in schools or universities and for universities to evaluate each canteen to create healthy and good canteens.